Hedging interest rate risk using simple, covariance-adjusted and volatility-adjusted immunization strategies : Japanese government bonds : April 1989 to December 2000 - Lim, Ming Siang (2008)
Assessing the relative performances between simple, covariance-adjusted and volatility-adjusted immunization strategies on a portfolio consisting of Japanese Government Bonds. The data collected for the Japanese Government Bonds cover the period between April 1989 and December 2000.